Arts and Culture in Building and Sustaining Peace (SIRJANĀ – A Journal Of Arts and Art Education, 2021)
Peace, harmony and development are essential conditions for any society, developed or developing, to progress. The 2011 World Development Report revealed that growing recognition of the link between social services, conflict and peace has helped in inclusion of social services’ provision in peace agreements. A report from ‘Policy Link’ gives equitable development as the key to peace. Music plays a great role in building peace in conflict situations, so does religion, media, performance, theatre. For achieving peaceful conditions there is a need to strike a balance between two extremes including inner and outer peace. Salzburg Global Seminar (2014) focused on using soft power, especially arts and culture, since cultural engagement helps transform perceptions. Case studies referred to in this write up provide sufficient evidence of the high usefulness of arts and culture in every phase of conflict. A detailed portfolio of case studies covering seven countries including Nepal of Asia describes the importance of ‘narratives’ and ‘story telling’, preservation of historical artifacts, photographs etc. for building peace mostly in post conflict stage. The researchers were of the view that the affected persons or beneficiaries needed to be involved right from the beginning of a peace project. British Council’s publication named ‘The Art of Peace’ emphasizes on the importance of local actors’ engagement as well as arts and cultural programs in linking culture, security and development. A project launched by the World Bank and the United Nations, entitled pathways to peace, offered guiding principles, namely, target institutional failure responsible for conflict, to be of inclusive nature, and form sustainable overtime character. Arts and Culture have a distinct place in resolving conflict thus it deserves adequate government support and a networking with other actors such as local municipalities, societies and groups.